Pass-colour: generating password coloured graphical assistance - Mohd Yasin, Anita; Mohd Isa, Mohd Ali; Hasrol Jono, Mohd Nor Hajar Hasrol Jono; Sardi, Janudin Sardi; za'ba, Nurmaisara (2007)
Regular text-based password was the most common method of authentication these days, but it often leads user to choose weak password. As a result, the password was easily broken or cracked through password dictionary attack or brute-force attack. Therefore, the objective of this study was to employ colour-based password authentication in order to provide secure and memorable password authentication. A prototype of this password authentication, called Pass-Colour, was proposed to enable the creation of a secure and memorable password based on colour. Based on the survey performed on fifty one offline respondents and nineteen online respondents, majority of the offline respondents thought that colour-based password authentication is not feasible and not memorable. However, majority of the online respondents who tested the prototype said that it is feasible and memorable. Overall, it is encouraging and has potential to be secured plus memorable password authentication. In spite of that, further study required to explore some aspect of this password authentication in the future.